(untitled) (Revista Sistemas de Producción Agroecológicos, 2024)
The article "Effect of agrochemicals on enzymatic activity of agricultural oil: A bibliographic revision" addresses the importance of soil enzymatic activity in the context of agriculture and the impact of agrochemicals on this activity. In view of the fact that agriculture is fundamental for the economy and food security, but intensive cultivation and the change from forest to cultivated soils have generated a negative impact on soil degradation, emitting large amounts of CO2 into the atmosphere, It is analysed the different types of agrochemicals used in agriculture, such as pesticides, insecticides, herbicides, as well as changes in the enzymatic activity of the soil, which is a key indicator of its health and quality. Therefore, a review of various studies from the period between 2002 and 2023 is carried out, which compile research related to the effects of agrochemicals on soil enzymatic activity and the possible mechanisms underlying these changes. Is thus, that among the results, the importance of understanding these effects and how they can alter the activity of the enzymes responsible for key processes, such as the decomposition of organic matter, the availability of nutrients and the regulation of the soil microbiota, stands out. Likewise, it is recommended to consider the implications of these findings in agricultural and environmental management, as well as in the promotion of sustainable practices that minimize the negative impact of agrochemicals on the enzymatic activity of the soil and on ecosystems in general.